Block-chain application Based Economic impact of Coronavirus pandemic on Medicine industry inventory System for Deteriorating objects with two-warehouse and wastewater treatment using PSO. (2022) - Singh Yadav, Ajay; Pandey, Garima; Kumar Arora, Tarun; Kumar Chaubey, Pavan
Abstract: In this paper, the determined economic impact of the Medicine industry of the Coronavirus pandemic for aggravating items with a ramp-type demand with inflation effects in two-warehouse storage devices and wastewater treatment cost using PSO is developed. The owned warehouse has a fixed capacity of W units; rented warehouse has unlimited capacity. Here, we hypothesized that the Block chain Economic Impact of the Coronavirus Pandemic Medicine Industry in Inventory Cost of Inventory in RW is greater than that in OW using PSO. The shortcomings of the economic impact of the Coronavirus pandemic Medicine industry are allowed and partially lagged behind, and it is assumed that Block chain's economic impact of the Coronavirus medicine pandemic industry decreases over time with a variable deterioration rate and wastewater treatment cost using PSO. The effect of inflation was also considered due to the different costs associated with Blockchain applying the Economic Impact of the Coronavirus Medicine Industry Inventory System and wastewater treatment cost using PSO. The numerical sample is also used to study the behavior of the model using particle size optimization. The cost minimization technique is used to obtain expressions for total costs and other parameters.